Interdisciplinary Applications of Kinematics Proceedings of the Third International Conference (IAK) - Kecskeméthy, Andrés; Geu Flores, Francisco; Carrera, Eliodoro; Elias, Dante A. (Mechanisms and Machine Science, 2019)
This is the proceedings of the Third Conference on Interdisciplinary Applications of Kinematics (IAK 2018) held in Lima, Peru, March 5-7, 2018. The conference brought together scientists from several research fields, such as computational kinematics, multibody systems, industrial machines, robotics, biomechanics, mechatronics, computational chemistry, and vibration analysis, and embraced all key aspects of kinematics, namely, theoretical methods, modeling, optimization, experimental validation, industrial applications, and design. Kinematics is an exciting area of computational mechanics and plays a central role in a great variety of fields and industrial applications nowadays. Apart from research in pure kinematics, the field deals with problems of practical relevance that need to be solved in an interdisciplinary manner in order for new technologies to develop. The results presented in this book should be of interest for practicing and research engineers as well asPh.D. students from the fields of mechanical and electrical engineering, computer science, and computer graphics.